2020
DOI: 10.1002/ptr.6613
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer activity and molecular mechanisms of α‐conidendrin, a polyphenolic compound present in Taxus yunnanensis, on human breast cancer cell lines

Abstract: α-Conidendrin is a polyphenolic compound found mainly in Taxus yunnanensis, as the source of chemotherapy drug paclitaxel, which has been used in traditional medicine for treatment of cancer. This study aimed to investigate the anticancer activity and molecular mechanisms of α-conidendrin on breast cancer cell lines. The results of the present study show that α-conidendrin possesses potent antiproliferative effects on breast cancer cell lines MCF-7 and MDA-MB-231. α-Conidendrin significantly induced apoptosis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 52 publications
1
15
0
Order By: Relevance
“…The therapeutic regime using amorfrutin C shows considerable disruption of mitochondrial integrity, which results in an irreversible opening of mPTP in HT-29 cells [ 44 ]. There is increasing recognition of other nutraceuticals such as allyl isothiocyanate [ 212 ], α-conidendrin [ 213 ], dehydrobruceine B [ 214 ], frugoside [ 215 ], methyl caffeate [ 216 ], tetrahydrocurcumin [ 217 ], phloretin [ 218 ], and sesamol [ 219 ] for their anticancer capacities. These nutraceuticals demonstrate anticancer capacities through disruption of mitochondria through ROS production, Cyt C release, loss of mitochondrial membrane potential, and modulation of Bcl-2 family members, ultimately leading to mPTP opening and inducing cell apoptosis.…”
Section: Pharmacological Switches Of Mptp Opening/closing In Cancer T...mentioning
confidence: 99%
“…The therapeutic regime using amorfrutin C shows considerable disruption of mitochondrial integrity, which results in an irreversible opening of mPTP in HT-29 cells [ 44 ]. There is increasing recognition of other nutraceuticals such as allyl isothiocyanate [ 212 ], α-conidendrin [ 213 ], dehydrobruceine B [ 214 ], frugoside [ 215 ], methyl caffeate [ 216 ], tetrahydrocurcumin [ 217 ], phloretin [ 218 ], and sesamol [ 219 ] for their anticancer capacities. These nutraceuticals demonstrate anticancer capacities through disruption of mitochondria through ROS production, Cyt C release, loss of mitochondrial membrane potential, and modulation of Bcl-2 family members, ultimately leading to mPTP opening and inducing cell apoptosis.…”
Section: Pharmacological Switches Of Mptp Opening/closing In Cancer T...mentioning
confidence: 99%
“…Nanocurcumin was found to decrease the cytokine levels and as a result decreased the mortality and severity in patients with COVID-19. Hence, nanocurcumin has been suggested as a potential therapeutic agent in controlling inflammation or inflammatory diseases due to its anti-inflammatory and immune-modulatory properties [ 104 ]. Moreover, curcumin when loaded in solid-lipid nanoparticles have been found to be effective in treating LPS-induced sepsis by modulating the inflammatory pathways such as TLR4/2-NF-kB.…”
Section: Uses Of Nanocurcuminmentioning
confidence: 99%
“…ROS have been found to function as second messengers in the regulation of a variety of cellular processes such as cell proliferation, differentiation, and migration (Perillo et al, 2020; Redza‐Dutordoir & Averill‐Bates, 2016). Studies have indicated that ROS generation at high levels can be associated with the activation of cell death signaling pathways such as apoptosis (Hafezi, Hemmati, Abbaszadeh, Valizadeh, & Makvandi, 2020). It is well documented that ROS activate both the intrinsic mitochondrial and the extrinsic death receptor pathways of apoptosis (Perillo et al, 2020; Redza‐Dutordoir & Averill‐Bates, 2016).…”
Section: In Vitro Studies On the Anticancer Effects Of Morinmentioning
confidence: 99%
“…Shin et al (2017) associated with the activation of cell death signaling pathways such as apoptosis(Hafezi, Hemmati, Abbaszadeh, Valizadeh, & Makvandi, 2020). It is well documented that ROS activate both the intrinsic mitochondrial and the extrinsic death receptor pathways of apoptosis(Perillo et al, 2020;Redza-Dutordoir & Averill-Bates, 2016).…”
mentioning
confidence: 99%